Prostate cancer-specific death in brachytherapy treated high-risk patients stratified by pre-treatment PSA - Merrick, Gregory S.; Galbreath, Robert W.; Butler, Wayne M.; Fiano, Ryan; Adamovich, Edward (Journal of Contemporary Brachytherapy, 2017)
Purpose: To evaluate prostate-cancer specific mortality (PCSM) in a cohort of high-risk patients treated with a permanent prostate brachytherapy approach, stratified by pre-treatment PSA. Material and methods : 448 high-risk patients (NCCN criteria) underwent permanent prostate brachytherapy. High risk patients were stratified by pre-treatment PSA (≤ 10.0, 10.1-20, and > 20 ng/ml). Biochemical failure (BF), prostate cancer-specific mortality (PCSM), distant failure (DM), and overall mortality (OM) were assessed as a function of prognostic group. Multiple clinical, treatment, and dosimetric parameters were evaluated for impact on outcome. Results : The 10-year OM, BF, and PCSM for the entire cohort were 28.5%, 13.3%, and 4.9%, respectively. At 10 years, PCSM was 2.5%, 10.7%, and 4.5% in the PSA ≤ 10, 10.1-20, and > 20 ng/ml groups, respectively. No statistically significant differences in BF or overall survival (OS) were noted when stratified by pre-treatment PSA. DF was the most common in the 10.1-20 ng/ml cohort (8.6% at 10 years). In multivariate analysis, PCSM was most closely related to percent positive biopsies (p = 0.001) and tobacco (p = 0.042). Conclusions : High-risk prostate cancer treated with permanent prostate brachytherapy and supplemental external beam radiotherapy resulted in excellent long-term biochemical control and PCSM. Overall, PCSM was low in all cohorts but highest in the intermediate PSA group (10.1-20 ng/ml).